Green Tourism Sustainability: Optimization Of Original Regional Income By E-Money - Satia Utama, Anak Agung Gde; Khomsatin, Lilik (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to design a non-cash payment (e-money) system using B-CARD (Banyuwangi CARD) at tourism Website by Banyuwangi cultural and tourism service. This study uses the AIS (Accounting Information System) theory and electronic payment system (E-payment) theory. The purpose of B-CARD is as a method and payment system to be more effective and efficient. The research method uses qualitative by interviews, observation, and documentation. The analysis technique approach is input-process-output. The results of the study show that B- CARD can provide efficiency or saving time during tourist access transactions. Also, B-CARD can be used as a government effort to collect tourist fees for each tourist location with adjusted conditions. So that the B-CARD design can contribute to the effectiveness of local revenue and support green tourism sustainability in Banyuwangi.